Эволюция зеренной структуры аустенитной стали ЭК-164 в результате термомеханической обработки - Ким, Анна Владимировна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
The influence of high-temperature thermomechanical treatments (HTMT) on grain structure of reactor austenitic steel EK-164 has been studied. It is shown that as a result of hot deformation grains stretch in the rolling direction and flatten in the rolling plane with a decrease of their average size by several times. The studied HTMOs lead to an increase in yield strength with a decrease in relative elongation.